Prarancangan Pabrik Melamin Dari Urea Dengan Proses Low-Pressure Dengan Desain Alat Utama Packed Bed Scrubber (V-101) - Syaktia Aryuda; Sri Helianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Melamine is a chemical compound derived from urea as white crystals that raw material for making glue, household appliances. The estimation of melamine market in 2020 is 1,5.106 tons, and keep growth by 3% until 2026. A melamine plant is a necessity for Indonesia's domestic demand and for decreasing melamine import. We decided to conduct the preliminary plant design for melamine from urea. Our melamine plant has a capacity of 43,000 tons/year in JIIPE industrial park Gresik, East Java. This article is a summary report for Packed Bed Scrubber (V-101), design, one of principle equipment. Based on economic feasibility analysis, the Break-Even Point (BEP) of is 38%; Return On Investment (ROI) is 49%; Internal Rate of Return (IRR) is 26% and payback period (PBP) is 1.6 years. We recommend continuing to detail design this preliminary plant design.Keywords: economic analysis, melamine, urea, factory design